The recombinant nucleocapsid protein of Newcastle disease virus produced in yeast. - Jahanshiri, Fatemeh; Jalilian, Farid Azizi; Saidin, Syswan; Sekawi, Zamberi; Mohd. Yusoff, Khatijah (2010)

(untitled)
This invention provides the recombinant nucleocapsid protein of the Malaysian velogenic Newcastle disease virus strain AF2240. The invention relates to methods for producing recombinant nucleocapsid protein in a eukaryotic expression system, in particular in a yeast expression systems. Also disclosed by the present invention are eukaryotic expression plasmids and eukaryotic cells transformed therewith. Further embodiments of the invention relate to the recombinant nucleocapsid protein produced with the inventive method and itss respective uses in the development of agents for the diagnosis of Newcastle disease.